Standard of notifications associated with anemia in the period 2019 to 2021 (Research, Society and Development, 2023)
Anemia is a pathology characterized by reduced erythrocyte and hemoglobin mass, which may result in low tissue oxygenation. In patients with COVID-19, this condition proved to be important because it represents a possible risk factor. This is a descriptive observational epidemiological study, with a quantitative approach, carried out with data obtained on the DATASUS platform, which were analyzed and statistically compared. The objective was to draw a sociodemographic profile of patients affected by anemia of different etiologies between 2019 and 2021, the years of the pandemic in Brazil. As a result, hospitalizations due to anemia were highlighted in the Southeast region, especially in the state of São Paulo, and emergency hospitalizations prevailed over elective ones. In addition, the female, brown and elderly population (over 60 years old) was the most prevalent in the reported cases, and the only macro-region in which the numbers of hospitalizations dropped continuously, from 2019 to 2021, was the South Region. This information allows the creation of an epidemiological profile of anemia and the identification of its incidence forms to apply the findings in the context of a patient with COVID and establish a temporal parallel between these two conditions and their correlation to clinical worsening.